2023
DOI: 10.1186/s13098-023-01208-5
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of continuous glucose monitoring with FreeStyle Libre® in Brazilian insulin-treated patients with types 1 and 2 diabetes mellitus

Luciana Bahia,
Karla F. Mello,
Lívia Lovato Pires Lemos
et al.

Abstract: Background Hypoglycemia is a barrier to optimal glucose control in the treatment of both type 1 (T1DM) and type 2 diabetes mellitus (T2DM). Blood glucose monitoring is essential in diabetes management. Inappropriate glucose management is associated with high mortality and morbidity. FreeStyle Libre® (FSL) is a continuous glucose monitoring (CGM) system that provides effective, safe, and convenient glucose monitoring, without routine finger pricking. This study aims to estimate the incremental c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…There are no published data regarding the cost-effectiveness of CGM devices in inpatient settings. Other studies that focused on an outpatient comparison between CGM and CBG showed that CGM was associated with an incremental cost-effectiveness ratio (ICER) of £3684/Quality Adjusted Life Year (QALY) in a United Kingdom population [ 6 ], an ICER of R$39,692.67/QALY in Brazilian type 2 diabetes patients [ 7 ], and €180,553/QALY in a Spanish meta-analysis [ 8 ]. Unfortunately, the previous efficacy study [ 5 ] showed no difference regarding inpatient mortality, infection, or length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…There are no published data regarding the cost-effectiveness of CGM devices in inpatient settings. Other studies that focused on an outpatient comparison between CGM and CBG showed that CGM was associated with an incremental cost-effectiveness ratio (ICER) of £3684/Quality Adjusted Life Year (QALY) in a United Kingdom population [ 6 ], an ICER of R$39,692.67/QALY in Brazilian type 2 diabetes patients [ 7 ], and €180,553/QALY in a Spanish meta-analysis [ 8 ]. Unfortunately, the previous efficacy study [ 5 ] showed no difference regarding inpatient mortality, infection, or length of stay.…”
Section: Discussionmentioning
confidence: 99%